Optimization of the Raising of Satintelkam Kamneg Unit to Prevent the Spread of Radicalism in the Jurisdiction of the Grobogan Police - Lumban Raja, Gihon Sahatma Togu (Advances in Police Science Research Journal, 2024)
The focus of the research in this final project is optimizing the Unit performance in early detection to prevent radicalism in Grobogan Regency This research is important because the number of raising targets in Grobogan Regency has increased over the last 4 years, so that the Kamneg Unit is trying to optimize the raising that is being carried out so that it is in accordance with Perkabik No.3 of 2013 concerning Raising Police Intelligence. This research aims to: (1) describe the organizational resources of the State Security Unit to prevent the spread of radicalism, (2) describe and explain the Kamneg Unit’s raising management system to prevent the spread of radicalism. To analyze the problems above, several theories are used in this research, namely Organizational Resource theory and Management theory. While the concept used, namely; the concept of Optimization, the concept of Raising, the concept of Intelligence, and the concept of Crime Prevention, and the concept of Radicalism. In this research used qualitative methods with descriptive analysis to process data and field research to obtain data directly. Primary and secondary data sources use data triangulation to obtain data validity. The findings during this research were (1) The Kamneg Unit’s organizational resources did not meet the expected criteria, such as personnel who had not attended training, insufficient budget, inadequate fundraising methods, and damaged special intelligence tools, (2) the management system for raising is not optimal, such as planning that is not appropriate, personnel placement that is not supported by the number of personnel, coordination that is not good and supervision of product manufacturing that is lacking The conclusions in this research are, (1) Inadequate organizational resources, must be increased for the implementation of fundraising (2) The management system for fundraising that is not optimal, needs to be adjusted to Perkabik No. 3 of 2013.